ANALISIS UPAYA PENANGKAPAN IKAN PELAGIS KECIL DI SELAT MAKASSAR, PERAIRAN PANTAI BARAT SULAWESI SELATAN - Alfa F.P Nelwan; M. Fedi Sondita; Daniel R. Monintja; Domu Simbolon (Fakultas Perikanan dan Ilmu Kelautan, 2010)
Fishing effort can be regarded as a total mobilized capability made by fishing fleet to produce catch. There are 8 types of significant fishing units operated in Makassar Strait, off west coast of South Sulawesi Province; these are boat seines, beach seines, purse seines, drift gillnets , encircling gillnets, set gillnets, boat liftnets and fixed liftnets. Annual total fishing effort made by the 8 types of fishing units over a period of 30 years (1977-2006) were calculated after standardization considering variability in capture capacity among them. An analysis was carried out to identify fishing effort dynamics in three predefined fishing sub-areas: around Spermonde Islands (zone A), off Polmas and Pinrang District (zone B) and off Majene and Mamuju District (zone C), especially to concidering capture fisheries condition within four predefined development periods: (1) motorization program (1977-1982), (2) credit loan program (1983-1990), (3) coastal community empowerment program (1991-1997), and (4) desentralized fisheries management (1998-2006). Fishing effort increases and fishing units productivity decrease over a period of thirty years period